Safe-Asset Shortages: Evidence from the European Government Bond Lending Market. (20th December 2021) - Aggarwal, Reena; Bai, Jennie; Laeven, Luc
Abstract: We identify the unique role of the government bond lending market in collateral transformation during periods of market stress. Using a novel database, we provide evidence that safe assets in the lending market have higher demand, higher borrowing cost, and higher usage of noncash collateral relative to nonsafe assets during stressed market conditions. Moreover, we find that market participants are able to obtain safe assets using relatively low-quality noncash collateral, allowing for collateral transformation. We show that policy interventions by central banks can help reduce safe-asset shortages by returning sought-after safe assets to the market.